2010
DOI: 10.1021/la103193m
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Macroscopic Interfacial Dynamics between Clathrate Hydrates and Surfactant Solutions

Abstract: Macroscopic interfacial interactions between cyclopentane (CP) hydrates and various surfactants droplets are examined in a CP/n-decane oil mixture. Initial contact force and subsequent z-axis dependent retraction force are measured utilizing a high-resolution microbalance integrated with a micrometer-precision stage. The resulting retraction force is utilized to determine the overall adhesion energy of the system. In addition, interfacial tensions and contact angles of the system are examined to further unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 33 publications
2
73
2
Order By: Relevance
“…The impact of different concentrations of KHIs on interfacial tension/surface tension has been studied and no changes due to the concentration were observed. It has been reported that for the nonionic surfactants (PVP and PVCap) the interfacial tension remains almost constant independent of the concentration (Song et al, 2010). They observed almost constant contact forces for all concentrations (100 ppme5000 ppm) between cyclopentane hydrates and the surfactant solution.…”
Section: Contact Anglesmentioning
confidence: 95%
“…The impact of different concentrations of KHIs on interfacial tension/surface tension has been studied and no changes due to the concentration were observed. It has been reported that for the nonionic surfactants (PVP and PVCap) the interfacial tension remains almost constant independent of the concentration (Song et al, 2010). They observed almost constant contact forces for all concentrations (100 ppme5000 ppm) between cyclopentane hydrates and the surfactant solution.…”
Section: Contact Anglesmentioning
confidence: 95%
“…22,[25][26][27][28] Hun et al also studied the interaction between hydrate particles and water in a temperature-controlled hydrocarbon environment utilizing an apparatus fabricated with a microbalance and z-axis stage. [29][30] Both groups explained the trends observed in the measured adhesion forces in terms of a capillary bridge formed between the contacting hydrate particles and/or hydrate particles and liquid droplets. More recently, Aspenes et al studied the adhesion forces between hydrate particles and a number of solid surfaces with various surface energies in the presence of water and/or other petroleum acids in an oil phase.…”
mentioning
confidence: 92%
“…4 These four steps to plug formation include: (i) water entrainment in the oil phase, (ii) hydrate shell growth at the water-oil interface, (iii) hydrate aggregation, and (iv) accumulation/plugging of hydrate particles and aggregates. [14][15][16] This work aims to investigate the interaction between water droplets and cyclopentane hydrate particles using a micromechanical force (MMF) apparatus. 1 Specifically, Fidel-Dufour 5 proposed a conceptual mechanism for agglomeration, which suggests that the interactions between unconverted water droplets and hydrate particles will play an important role at the early stage of the agglomeration.…”
Section: Introductionmentioning
confidence: 99%